Improvement of presentation performance through feedback - Dedy Setiawan (Politeknik Negeri Bali, 2021)
Presentation is a type of public speaking which requires special skills besides language competency. Presentation skill in English is a lesson or subject which can be found in some educational institutions in Indonesia. Besides presentation, public speaking can be in a form of speech, debate, and meeting. In public speaking, a speaker can face more than two people or even hundreds or thousands of people. While in ordinary conversation, the speakers and the listener called interlocutors are limited to only a few people. Presentation class is meant to improve the students’ performance in English public speaking. Feedback is usually given after a presentation activity is completed. In this case, the students who were trained were given feedback by the teacher. Feedback is given thoroughly on the language, content, and method of presentation. Research on feedback or assessment on oral presentation is underexplored. The present research is proof supported with empirical data which suggests that the role of feedback is important and statistically assessed as significant in making the later performance better. The main factor that determines the quality of a presentation is language skill. However, there are other aspects that are quite decisive such as the material or topic of the presentation and the presentation method.